Factors Related to the Incidence of Preeclampsia at RSD Tidore City - Jubaida Malagapi; Anik Purwati (International Journal of Medicine and Health, 2025)
Preeclampsia is a complex illness that can cause health issues and even death for both the mother and the fetus. The three signs of preeclampsia include elevated blood pressure (up to 140/90 mmHg), proteinuria (high protein in the urine), and edema. Preeclampsia is linked to a number of characteristics, including as parity, age, education, occupation, history of hypertension, multiple pregnancies, history of diabetes mellitus, and kidney disease. The purpose of this study is to identify the variables linked to the prevalence of preeclampsia in Tidore Regional Hospital patients who are pregnant or giving birth. This study employs a case control methodology and a descriptive analytical approach. Up to 132 respondents, comprising 66 case groups and 66 control groups, were sampled by accidental sampling. Medical records of moms who had preeclampsia were used as secondary data. A p-value of 0.001 (Sig. <0.05) indicated a relationship between parity and the incidence of preeclampsia; a p-value of 0.001 (Sig. <0.05) indicated a relationship between employment and the incidence of preeclampsia; a p-value of 0.000 (Sig. <0.05) indicated a relationship between the incidence of preeclampsia and a history of diabetes mellitus and kidney disease. preeclampsia at Tidore Regional Hospital with a p-value of 0.042 (Sig. <0.05).